KORELASI ANTARA INDEKS MASSA TUBUH (IMT) DAN TEKANAN DARAH PADA KOMUNITAS VEGETARIAN DEWASA DI KOTA PEKANBARU - Pradigdo, Gilang; ", Suyanto; Haslinda, Lilly (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTA vegetarian diet has grown rapidly into a global lifestyle for many years. Vegetarian diets typically tend to be lower in total fat, saturated fat, and total cholesterol, and high in fiber. Nutrients Intake were estimate as a factor that have corelation to BMI (Body Mass Index) and also blood pressure. This research aimed to gaining the correlations between BMI and blood pressure of vegetarian community in Pekanbaru. The design of this research was analytic correlative by analyzing the data obtained from community of vegetarian in Pekanbaru. Data collected as the result of community members’ health examination. The result showed that, there was no significant difference in BMI (p=0,734), systolic blood pressure (p=0,579) and diastolic blood pressure (p=0,123) between vegan and non-vegan. This research indicate statistically significant correlations between BMI with systolic blood pressure (r=0,672; p<0,001) and diastolic blood pressure (r=0,466; p=0,007) in community of vegetarian in Pekanbaru.Keyword : Vegetarian, Vegan, Non-vegan, Body Mass Index (BMI), blood pressure